Penerapan Konseling dengan Model KKJ (Kesalehan Keberislaman, Kecerdasan Finansial, dan Jiwa Sosial) dalam Meningkatkan Konsep Diri pada Remaja di Lembaga Pembinaan Khusus Anak Kelas I Palembang - Prabandari, Restri Ayu; Sujarwo, Sawi (Yayasan Kawanad, 2025)
This study examines the effectiveness of counseling interventions using the KKJ model (Islamic Piety, Financial Intelligence, and Social Spirit) to improve the self-concept of adolescents at Palembang Class I Special Child Development Institution (LPKA). Adolescents in correctional facilities often experience negative self-concept due to dysfunctional family backgrounds, weak economic conditions, and unsupportive social environments. A descriptive qualitative approach was employed with four male subjects aged 16-19 years from different legal backgrounds, including theft, child protection violations, narcotics abuse, and homicide. Data were collected through direct observation, in-depth interviews, and documentation over two months. The results revealed significant improvements across three dimensions of self-concept: self-knowledge, future expectations, and self-assessment. Subjects experienced positive behavioral transformations, including increased self-confidence, enhanced social skills, emotional stability, and spiritual awareness. The KKJ model proved effective in forming healthier, more psychologically and spiritually adaptive self-concepts among adolescent detainees. This integrated approach addresses cognitive, communicative, and spiritual domains simultaneously, providing a holistic rehabilitation framework. The findings suggest that value-based counseling can successfully transform adolescents from psychologically vulnerable individuals into resilient persons ready for social reintegration